A tale of hydrogen abstraction, initially detected via X‐ray diffraction. Issue 3 (15th March 2014) - Hui, Alice K.; Chen, Chun‐Hsing; Terwilliger, Adam M.; Lord, Richard L.; Caulton, Kenneth G.
<x xml:space="preserve">Abstract</x> Reaction of a bis‐tetrazinyl pyridine pincer ligand, btzp, with a vanadium(III) reagent gives not a simple adduct but dichlorido{3‐methyl‐6‐[6‐(6‐methyl‐1, 2, 4, 5‐tetrazin‐3‐yl‐κN2)pyridin‐2‐yl‐κN]‐1, 4‐dihydro‐1, 2, 4, 5‐tetrazin‐1‐yl‐κN1}oxidovanadium(IV) acetonitrile 2.5‐solvate, [V(C11H10N9)Cl2O]·2.5CH3CN, a species which X‐ray diffraction reveals to have one H atom added to one of the two tetrazinyl rings. This H atom was first revealed by a short intermolecular N...Cl contact in the unit cell and subsequently established, from difference maps, to be associated with a hydrogen bond. One chloride ligand has also been replaced by an oxide ligand in this synthetic reaction. This formula for the complex, [V(Hbtzp)Cl2O], leaves open the question of both ligand oxidation state and spin state. A computational study of all isomeric locations of the H atom shows the similarity of their energies, which is subject to perturbation by intermolecular hydrogen bonding found in X‐ray work on the solid state. These density functional calculations reveal that the isomer with the H atom located as found in the solid state contains a neutral radical Hbtzp ligand and tetravalent d1 V center, but that these two unpaired electrons are more stable as an open‐shell singlet and hence antiferromagnetically coupled.